Experimental investigation on the physical and mechanical properties enhancement of red clay modified with “RoadyesTM” - Quan Shen; Yuhang Lv; Gai Liu; Liuyiyi Yang; Zhaohui Wang (PLoS ONE, 2025)
This study investigates the enhancement of the physical and mechanical properties of red clay from the Zhuzhou region using a nano polymer material (RoadyesTM), cement, and lime. The effects of varying dosages of RoadyesTM, cement, and lime on the properties of the modified red clay are examined. The indicate reveal that: (1) the addition of RoadyesTM alone results in a reduction in both the liquid limit and plasticity index, while simultaneously increasing cohesion and unconfined compressive strength; (2) Red clay treated with 0.25% RoadyesTM demonstrates the highest compression index, indicating optimal compressibility.; (3) The combination of RoadyesTM with cement and lime significantly enhances the mechanical properties of the red clay. Specifically, the combinations of 0.25% RoadyesTM with 6% cement and 0.25% RoadyesTM with 7% lime lead to the most significant improvements in both cohesion and compressive strength, with only minor changes in the internal friction angle. Additionally, it is found that the optimal dosage of cement decreases by 9% when RoadyesTM is incorporated.; (4) The effectiveness of the combination of 0.25% RoadyesTM and 6% cement is notably superior to that of the combination with 7% lime. Overall, the results of this provide offer valuable insights for the design and construction of roadbed engineering involving red clay.